Defining economic security through literature review - Yuzue, Natsuya; Sekiyama, Takashi (Frontiers in Political Science, 2025)
With the expansion of the global economy and the development of technology, the concept of economic security has attracted attention, as highlighted at the G7 Hiroshima summit in 2023. Although this is important for policies, it has not yet been clearly defined. This definition cannot be neglected when evaluating policies that ensure that private economic activities are not excessively restricted. Therefore, this study aims to define economic security concerning value, threats and means. This study used literature reviews to analyze eight Japanese and four English studies. Economic security can be defined as the protection of essential values, such as national survival, sovereign independence, and economic prosperity, from threats, including the disruption of critical commodity supplies, the outflow of advanced technologies, and overreliance on other countries This can be achieved through diversifying supply sources and supply chains, diplomatic efforts to maintain a free and open international economic system, stockpiling essential resources, reducing excessive foreign dependence, developing indispensable goods domestically, and preventing the loss of critical advanced technologies. This study also argues that regulatory measures must be necessary and reasonable to eliminate threats to the values that need protection, because restrictions imposed for economic security purposes limit the freedom of business activity. The definition of economic security and the reflections on economic security policy presented in this paper contribute to the broader discussion in international political economy.